Bronchoalveolar Lavage (BAL) in Pulmonary Alveolar Proteinosis and Sarcoidosis - Prasenohadi Prasenohadi (Jurnal Respirologi Indonesia, 2023)
Bronchoalveolar lavage (BAL) is a minimally invasive procedure using flexible fiber optic bronchoscopy guidance that is safe, easily performed, and well tolerated. Bronchoalveolar lavage procedure is important to diagnose or differentially diagnose patients with a clinical appearance and radiological findings that are not specific. Mechanisms related to lung disorders such as inflammation, fibrosis, and abnormal material could be obtained by BAL fluid. Non-infection lung disorders such as pulmonary alveolar proteinosis (PAP) and sarcoidosis may be diagnosed by BAL. BAL in non-infection lung disease has diagnostic and therapeutic functions. As diagnostic function, BAL could be a tool to obtain a lower respiratory tract sample, and lavage from the respiratory track could be a therapeutic function of BAL.